Державне регулювання малого агробізнесу в Україні: значення та перспективи - Байдак, Ірина Іванівна; Baidak, Irina (Publishing House “ACCENT”, 2019)
Розвиток аграрного підприємництва в Україні, особли-во в умовах гострої конкуренції, техніко-технологічних змін виробництва неможливий без ефективного держа-вного регулювання. Формування сприятливого інсти-туційного забезпечення для розвитку малого аграрного підприємництва в Україні потребує врахування значу-щості неформальних інститутів та пошуку механізмів їх удосконалення. The development of agricultural entrepreneurship in Ukraine, especially in conditions of fierce competition, technical and technological changes in production is impos-sible without effective government regulation. The for-mation of favorable institutional support for the develop-ment of small agricultural entrepreneurship in Ukraine re-quires taking into account the importance of informal insti-tutions and finding mechanisms for their improvement.
State regulation of small agribusiness in Ukraine: significance and prospects
Keywords: агробізнес; agribusiness; сільські території; rural areas; мале аграрне підприємництво; small agrarian entrepreneurship; кооперація; cooperation; державне регулювання; government regulation